'It's the ultimate observer role…you're feeling and seeing what's happening to you': students' experiences of peer simulation. (29th October 2020) - Pritchard, Shane A; Dalwood, Narelle; Keating, Jennifer L; Nestel, Debra; Te, Maxine; Blackstock, Felicity
Abstract : Introduction: Simulation-based education (SBE) benefits learners, but multiple barriers limit curriculum integration. Peer simulation, where students are formally educated to portray patient roles in simulated interactions with their peers, might maintain the educational benefits of SBE, be cost-effective, and enable additional learning. Our research question was: 'What are the perspectives and experiences of physiotherapy students who participated in peer simulation?'. Methods: Second-year physiotherapy students (n=16) participated in a blended peer simulation programme that included preparation for patient role portrayal and simulated clinical interactions with peers. Using an interpretivist approach, students' experiences and perspectives were explored in two focus groups. Inductive thematic analysis was completed by two researchers. Results: Three primary themes were identified that characterised the experiences and perspectives of physiotherapy students: peer simulation is a valuable learning experience, specific design features enable effective peer simulation, and portraying a patient provides unique insight. Peer simulation was unexpectedly realistic, revealed knowledge and skill deficits, and improved their clinical skills. Specific design features included consistent engagement, repetitive, individualised practice, multiple forms of feedback, and detailed role preparation. Being the patient in peer simulation gave students unique and valuable insight into patients' experiences of and feelings about health issues and healthcare interactions. Conclusion: Physiotherapy students acquire new insights during peer simulation that may enrich their capabilities for practice through understanding healthcare interactions from patients' perspectives. Physiotherapy students' learning in peer simulation appears to align with the powerful learning experiences of health professional students in other immersive simulation modalities.